Intercom 2000 /Anna Uhl Chamot - Uhl Chamot, Anna (Estados Unidos de América: Heinle &Heinle, 1990)
Intercom 2000 is a four-level basic course featuring a spiraled approach to language learning with presentation, reinforcement, expansion, and regular review of communication forms and structures
MAKING ENDS MEET, A NEW APARTMENT, ON THE ROAD.
Incluye Indice
duc|}0053
Keywords: WHAT DID YOU DO LAST WEEKEND?, IS THERE A BANK NEAR HERE?THIS BOOK IS FOR STUDENT OF UNIVERSITY.|Col.